Rancang Bangun E-Learning Simulasi Digital bagi Siswa SMK Kesehatan Parigi Pangandaran - Lilis Mulisah; Sarmidi Sarmidi; Hani Rubiani (JURNAL ILMIAH NUSANTARA, 2025)
The rapid development of information technology has encouraged a paradigm shift in the education sector, particularly at the vocational secondary level. SMK Kesehatan Parigi Pangandaran faces challenges in delivering the Simulasi Digital subject effectively due to the predominant use of conventional teaching methods. This study aims to design and develop a web-based e-learning system specifically for Simulasi Digital learning using the ADDIE instructional design model. The system includes features for material management, interactive simulations, automatic quizzes, and progress reporting. The research employed a Research and Development (R&D) approach with needs analysis, system design, development, implementation, and evaluation stages. The implementation results show that the e-learning system improved students’ comprehension, facilitated teachers in delivering material, and created a modern, responsive learning environment. The developed system is expected to be a digital solution for interactive, flexible learning that meets 21st-century educational demands.